An Effective Trust-aware Authentication Framework for Cloud Computing Environment - SaboutNagaraju, SaboutNagaraju; Jayakumar, S.K.V (International Journal of Computer Sciences and Engineering, 2018)
Although cloud computing has become one of the basic utility in ICT era with several benefits like rapid elasticity, resource pooling broad network access, and on-demand self-service, it introduces dozens of dirty security threats too. An effective authentication protocol is the basis, topmost prioritized and emergence one for the secure cloud communications. As a result, in this article an effective trust-aware authentication framework is proposed based on n-party multi-linear key pairing functions, trust and reputation aggregation functions and time-based dynamic nonce generation. In addition to formulating an effective authentication protocol, we have analyzed the mutual authentication and formal security strength by using cryptographic GNY belief logic which will prove proposed protocol not only meets intended mutual authentication, but also justifies the security strength against the impersonation and ephemeral secret leakage attacks.